First clinical experience of combined treatment of patients with atrial septal defect and atrial fibrillation using a two-staged approach - A. O. Kovalchuk; T. V. Kravchenko; S. I. Estrin; S. O. Antonyuk; Y. S. Akobirov; O. V. Chizhikova (Ukrainian Journal of Cardiovascular Surgery, 2018)
Atrial septal defect (ASD) is pathophysiologically associated with atrial fibrillation (AF) development, so this requires an integrated approach in treating patients with these both pathologies.Aim of work: on the basis of some clinical cases to study the efficiency of catheter radiofrequency ablation (RFA), performed before the surgical ASD closure, in treating AF.Materials and methods. In 2015-2017 5 consecutive adult patients having secondary ASD combined with recurrent medically refractory AF have been treated. Prior to ASD closure each patient underwent catheter RFA in left atrium (LA) using a circular pulmonary vein antral isolation approach and additional lesions, while the ablating catheter was introduced into LA via septal defect. In terms from 1 (n=2) up to 3 (n=3) months after RFA each patient underwent surgical ASD closure with autopericardial patch by dint of artificial circulation.Results and discussion. AF has been successfully eliminated after RFA in all cases. All patients were given amiodaronum 200 mg/day. After 1 month it was discontinued in 3 patients wich had control catheter procedure after 3-month postablation with additional lesions in abnormal activity areas. Other 2 patients, due to the significant changes in atrial myocardium, had an uncertain prognosis as to keeping the sinus rythm witout therapy, so the surgery was provided after 1-month postablation, and amiodaronum has been held up to present. No recurrent events of AF have been registered in all cases before the surgery. Each patient underwent successful operative closure of ASD. In terms from 3 to 18 months of post-operative follow-up all patients has preserved sinus rythm.Conclusions. In patients with both medically refractory AF and amenable to operative closure secondary ASD a staged approach with catheter RFA preceeding surgery is an acceptable alternative to combined surgical procedure.